Two novel models evaluating the determinants of resting metabolic rate in Indian children - Sandra Aravind Areekal; Anuradha Khadilkar; Neha Kajale; Arun S. Kinare; Pranay Goel (Human Biology and Public Health, 2023)
Background: Resting metabolic rate (RMR) quantifies the minimal energy required to sustain vital body functions and is a crucial component of childhood development. Mean RMR per unit body mass (RMR/BM) has very accurately been modelled in references for Caucasian adolescents. Objectives: Here we address the extent to which such a model can be adapted to explain RMR/BM in Indian children. Subjects and Methods: The multicenter study (MCS) is a cross-sectional dataset on 495 children (235 girls and 260 boys) aged 9 to 19 years with anthropometric, body composition, and RMR measurements. The RMR-ultrasonography study (RMR-USG) consists of anthropometric data, RMR, and liver and kidney volume measured through ultrasonography in nine girls and nine boys aged 6 to 8 years. Results: The mean RMR/BM in Indian children is significantly lower compared to their Caucasian counterparts, except in boys in the age group 9–13 years. We present two novel phenomenological models that describe the mean RMR/BM stratified by age in Indian children and adolescents. The first is a modified Wang model in which the relative masses of four major organs are assumed to be uniformly lowered for Indian children. Theoretical predictions of liver size are not uniformly borne out in a pilot validation study; however, the relative mass of the kidney is found to be significantly lower. The second model demonstrates that changes in body composition alone can also explain the Indian data. Conclusion: A modified Wang model in which the relative masses of four major organs are assumed to be uniformly lower in Indian children and differences in body composition can be used to estimate mean RMR/BM by age in Indian children; however, understanding the mechanistic basis of variation in RMR/BM remains an open problem.